2019
DOI: 10.1021/acscatal.8b04828
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Nonstructural Ligands to Zirconia-like Metal–Organic Framework Nodes To Tune the Activity of Node-Supported Nickel Catalysts for Ethylene Hydrogenation

Abstract: Previous work has shown that introduction of hexafluoroacetylacetone (Facac) units as nonstructural ligands for the zirconia-like nodes of the eight-connected metal−organic framework (MOF), NU-1000, greatly alters the selectivity of node-supported oxynickel clusters for ethylene dimerization vs oligomerization. Here we explore a related concept: tuning of support/catalyst interactions, and therefore, catalyst activity, via parallel installation of organic modifiers on the support itself. As modifiers we focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 74 publications
8
90
0
2
Order By: Relevance
“…In the case of NU-1000, SALI approach takes advantage of the ability of the Zr 6 nodes to be altered through the reaction between the free Zr-OH moieties (labile -OH and H 2 O ligands) and introduced nonstructural organic ligands. 90 The functional ligands may be carboxylic acid containing molecules, [265][266][267][268][269] phosphonic acid containing molecules, 270 or perfluoroalkane chains, 271 in which their addition in NU-1000 results in enhanced activity in different catalytic reactions. Moreover, the further modification of the ligands with varying electron-donating or electron-withdrawing groups can be performed to tune the electronic environment provided by the Zr 6 nodes.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of NU-1000, SALI approach takes advantage of the ability of the Zr 6 nodes to be altered through the reaction between the free Zr-OH moieties (labile -OH and H 2 O ligands) and introduced nonstructural organic ligands. 90 The functional ligands may be carboxylic acid containing molecules, [265][266][267][268][269] phosphonic acid containing molecules, 270 or perfluoroalkane chains, 271 in which their addition in NU-1000 results in enhanced activity in different catalytic reactions. Moreover, the further modification of the ligands with varying electron-donating or electron-withdrawing groups can be performed to tune the electronic environment provided by the Zr 6 nodes.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Moreover, the further modification of the ligands with varying electron-donating or electron-withdrawing groups can be performed to tune the electronic environment provided by the Zr 6 nodes. 267 SALI-modification of NU-1000 can be performed with an organic ligand, 268 or a metal complex featuring an organic ligand. 269 NU-1000 functionalized by 5,5di-thio-bis(2-nitrobenzoic acid) ligand (DTNB@NU-1000) was found to be catalytically active for the degradation and subsequent detection of a nerve agent, which was observed by the release of the chromophore degradation product by visual inspection of filtered samples.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Although the variations for some substituents were small, the overall trend illustrated that the presence of an electron‐withdrawing group, especially a nitro group—the strongest typical electron‐withdrawing group, clearly shifted the binding energy to a lager value, agreeing well with a previous report. [ 13 ] When using Hammett's σ m values to describe the electronic effects of these substituted ligands, an H‐SALR was identified (Figure 2c), which is a typical one in the field of quantitative structure–activity relationship. The positive correlation indicated that a negative charge developed during the rate‐limiting step of the reaction.…”
Section: Figurementioning
confidence: 99%
“…[ 5 ] Atomic layer deposition has been used to control the formation of nanoparticles within MOF pores. [ 6 ] However, this approach requires specialized equipment and expensive volatile metal precursors. Alternately, MOFs have been grown directly on metallic nanoparticles, leading to core–shell structures.…”
Section: Introductionmentioning
confidence: 99%